Coupling Indonesian indigenous Citrobacter freundii and Chlorella pyrenoidosa strain on the anode of microbial fuel cell with various substrates - IRFAN ANWAR FAUZAN; ANJA MERYANDINI; RONI RIDWAN; RUSLI FIDRIYANTO; NI WAYAN SRI AGUSTINI; DWI ANDREAS SANTOSA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fauzan IA, Meryandini A, Ridwan R, Fidriyanto R, Agustini NWS, Santosa DA. 2022. Coupling Indonesian indigenous Citrobacter freundii and Chlorella pyrenoidosa strain on the anode of microbial fuel cell with various substrates. Biodiversitas 23: 2471-2481. Microorganism plays a crucial role in the development of MFC systems. Indigenous to Indonesia, Citrobacter freundii GBH253 is a potential exoelectrogenic bacterium that could be developed into an MFC system. Coupling C. freundii GBH253 with potentially electricity-producing microalgae indigenous to Indonesia, such as Chlorella pyrenoidosa INK, in the anode of an MFC, could result in a more stable and higher electricity output. This study used C. freundii GBH253 and C. pyrenoidosa INK to produce electricity in various substrates. This research was conducted using a Factorial Randomized Block Design and Tukey’s test to determine significant differences between treatments. The result shows that electricity was generated in all treatments. The Bacterium-microalgae combination in acetate substrate can generate power density up to 211,97 mW m-2 and is the most stable compared to others. Bacterium dominates the electricity production in this combination, but the microalgae also play a role in producing electricity and increasing Chemical Oxygen Demand. The pH value of all treatments was higher than 7. Volatile Fatty Acids, like acetate and phenol, were produced in all treatments, whereas butyric acid and propionic acid were produced in several treatments. The Pearson correlation showed that some VFAs are highly correlated with power density.